Job demand or resource? - Schrade, Franziska; Walczok, Marvin; Bipp, Tanja (Zeitschrift für Arbeits- und Organisationspsychologie, 2026)
Artificial intelligence (AI) can function both as a job demand and as a job resource, with crucial implications for employees' well-being and motivation. However, research has not yet investigated how employees appraise AI in these terms and whether their appraisals are malleable. To fill this gap, we conducted an online experiment with 203 German white-collar workers. We randomly assigned the participants to a demand, resource, or control condition. The manipulation consisted of a focused reflection on AI either as a demand or a resource for the participant's current job. Results indicated that our induced focus did not significantly influence the participants' AI appraisal. Across experimental conditions, the participants appraised AI more as a resource than a demand (d = 1.05). These findings allow new insights into the appraisal of AI at work by distinguishing demand and resource appraisals, highlighting the robustness of AI appraisals, and suggesting that employees currently view AI primarily as supportive.